Kajian Dakwaan terhadap Tindak Pidana Penganiayaan yang Mengakibatkan Luka Berat (Studi Kasus Novel Baswedan) - Febiola, Stefany; Firmansyah, Hery (UNES Law Review, 2023)
In the series of actions carried out by the Defendant and Ronny Bugis, both were involved in an act that resulted in severe injuries to Novel Baswedan. The Defendant, as the main perpetrator, directly poured sulfuric acid onto Novel Baswedan's body. Meanwhile, Ronny Bugis, as an accomplice, was involved in the preparation and execution of the attack. From the perspective of criminal law, both can be considered perpetrators with roles in the planned assault resulting in severe injury to Novel Baswedan. Therefore, based on this analysis, the conclusion is that the judge's decision in the case of the assault on Novel Baswedan was based on appropriate legal considerations, taking into account all the facts and elements revealed during the trial. The judge correctly applied the relevant law in assessing the defendant's actions, considering the relevant elements of the criminal act, and delivering a verdict in accordance with the applicable legal rules.